When Do Teachers Respond to Student Feedback? Evidence from a Field Experiment - Margaretha Buurman; Josse Delfgaauw; Robert Dur; Robin Zoutenbier (Center for Economic Studies and ifo Institute (CESifo), 2020)
We ran a field experiment at a large Dutch school for intermediate vocational education to examine whether the response of teachers to student feedback depends on the content of the feedback. Students evaluated all teachers, but only a randomly selected group of teachers received feedback. Additionally, we asked all teachers before as well as a year after the experiment to assess their own performance on the same items. We find a precisely estimated zero average treatment effect of receiving student feedback on student evaluation scores a year later. However, teachers whose self-assessment before the experiment is much more positive than their students. evaluations do improve significantly in response to receiving feedback. We also find that pro-vision of feedback reduces the gap between teachers. self-assessment and students. assessment, but only to a limited extent. All of these results are driven by the female teachers in our sample; male teachers appear to be unresponsive to student feedback.
Keywords: C93; I20; M50; 330; field experiment; feedback; teachers; student evaluations; self-assessment; gender differences